Peningkatan Hasil Belajar Menggunakan Model Cooperative Tipe STAD Berbantuan Canva pada Pembelajaran Pendidikan Pancasila Kelas IV SDN 17 Batu Gadang Kota Padang - Siti Sara; Fikhen Tri Wulandari; Atri Waldi; Sherlyane Hendri (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to improve student learning outcomes through the STAD Cooperative model assisted by Canva in Pancasila Education learning for fourth graders at SDN 17 Batu Gadang, Padang City. This study is a Classroom Action Research (CAR) conducted in two cycles with stages of planning, implementation, observation, and reflection. The research subjects consisted of 26 fourth grade students, totaling 12 boys and 14 girls. Research data were collected through test and non-test techniques. The test instruments were in the form of essay and multiple-choice questions, while the non-test instruments included attitude and skill assessment rubrics, observation sheets for teacher and student activities, and documentation. Data were analyzed quantitatively using percentages for learning activities and RPPM, as well as analysis of averages and completeness of student learning outcomes, while qualitative data from observation results were used to strengthen the interpretation of the results in each cycle. The results of the study showed an increase in all aspects, namely teacher activity increased from 89.25% in cycle I to 96.4% in cycle II, student activity from 87.45% to 96.4%, and RPPM from 89.55% to 95.8%. Student learning outcomes also increased from an average of 62% in the first meeting of cycle I to 75.6% in the second meeting, and reached 91.2% in cycle II. Thus, the STAD Cooperative model assisted by Canva is effective in improving student learning outcomes.